Safe practice for childbirth in a university hospital - Maxuel Cruz dos Santos; Vitória Sandri Pedroni; Franciela Delazeri Carlotto; Silvana Cruz da Silva; Helga Geremias Gouveia; Letícia Becker Vieira (Universidade Federal de Santa Maria, 2020)
Objective: to identify the application of the essential practices of the World Health Organization Checklist for Safe Births (CLSB) performed in a University Hospital. Method: a descriptive cross-sectional study, carried out from January to October 2018, with 51 professionals who assist in labor, delivery and puerperium. To identify the applied practices, a semi-structured questionnaire and statistical analysis were used. Results: practices related to the use of drugs, availability of material resources, identification of abnormal bleeding, skin-to-skin contact, breastfeeding and reproductive planning are as recommended. However, there was no standardization regarding the evaluations in the partogram and the orientations to women and companions about the signs of worsening. Conclusions: the CLSB presents itself as an innovative tool in obstetric care. It offers opportunities for improvement and qualification of care, standardizing essential conducts, such as guidelines on clinical signs and registration in the partogram, favoring the safety of the mother-baby binomial.